Gaya kepemimpinan transformasional dan situasional di perpustakaan akademik - Rifauddin, Machsun; Munardji, Munardji; Halida, Arfin Nurma; Kholis, Nur (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. In academic libraries, transformational and situational leadership is important as it can change organizational behavior and increase the staff performance.There is limited discussion types of leadership. This research discusses two types of leadership and develops a framework in academic libraries of ideal leadership. Data Collection Method. The paper used a qualitative approach and considered literature review from books, journals, and other sources related to the theme. Data Analysis. The paper analyzed various literature, examined and selected data, developed a theoretical framework, and conceptualized the contents. Result and Discussions. Transformational leadership in the academic library is appropriate to create a vision, however, staff commitments develop slowly. The leadership can be appropriately applied to the academic library with a few human resource as itemphasizes two-way communication to motivate staff. Meanwhile, in the situational leadership, organizational vision can be achieved when staff commitments are developed effectively. The situational leadership can be implemented in the academic libraries with large number of staff by using direct and two-way interaction, as staff motivation may increase when they are trusted. Conclusion. The transformational and situational leadershipsare effective when applied to the proper circumstances to achieve set goals. Library leaders need to consider strengths and weaknesses of the leadership style.